Atribut-Atribut Sebuah Aplikasi Mobile Heathcare Bagi Pelanggan Di Indonesia - Aricson Simatupang; Didik Susilo; Ebenhard Agus Bandoro; Purnomo Purnomo; Widjoyo Pranapaw (Indonesian Business Review, 2018)
This paper is prepared with the objective of knowing the recommended health solutions features of mobile healthcare applications that will be offered to users of digital technology services based on their demographics, such as gender, age, income level, ownership of health insurance coverage and limited personal medical history. Research was conducted using 2 (two) methodologies, starting with qualitative approach by interviewing 12 respondents over the age of 30 years, middle-income and digital technology users to explore the issues related to current health services and alternative solution desires of some mobile application features health, and then followed by quantitative research through filling questionnaires on google form of 200 respondents sent email and whatsapp. From this research, we find most popular features of mobile health applications and have the potential to be developed further in the development of mobile health application business through the creation of market place related to the needs of doctor, ambulance, drug and patients.